Alcohol and work. Consensus Document of the La.R.A. (Workers representing a risk for others) group - Magnavita, Nicola; De Lorenzo, G.; Gallo, M.; Garbarino, S.; Goggiamani, A.; Janiri, L.; Messineo, A.; Miggiano, G.; Pichini, S.; Porpora, A.; Poscia, A.; Sacco, A.; et al. (La Medicina del Lavoro, 2014)
Aim: Current Italian legislation obliges employers to prevent workers who are occupationally at risk or who perform jobs that may be hazardous for the safety or health of third parties from consuming alcohol. The LaRA Group undertook to assess whether the law fully safeguards the health and safety of both workers and third parties, without impinging upon the civil rights of workers. Method: A written document expressing agreement was produced following discussions between doctors, lawyers, bioethicists and social partners. Results: There are gaps and inconsistencies in current laws; the differences in local and regional provisions prevent authorities from applying a single strategy at national level. There should be a change in existing rules under which the employer’s obligation to enforce the ban on consumption alcohol in the workplace is enacted solely by the “competent” physician whose institutional role is to safeguard and promote health. Some occupational categories that are subject to a ban on alcohol consumption do not currently undergo health surveillance. For example, if road transport drivers are not exposed to a specific occupational risk foreseen under another law, they can be placed under health surveillance only in those regions where the local laws contemplate this type of control. In other cases, the practice of assessing the risk to third parties and providing for compulsory health surveillance in the Risk Assessment Document, is considered by some jurists to be a “consuetudo praeter legem” and therefore acceptable in a field not yet covered by a specific law, but to be “contra legem” or unlawful by other jurists. Moreover, the competent physician who uses a breathanalyser or tests for alcohol addiction faces an ethical dilemma, since by communicating the results to an employer or authorities responsible for the issuing of licenses, he may be violating his professional oath of secrecy. Furthermore, the emphasis placed on testing has induced companies and inspectors to overlook educational and rehabilitation aspects. It is essential to involve general practitioners, educators and specialist services in addressing the problems of alcohol abuse so as to inform/train, recover and rehabilitate. The few studies available indicate that the rules are poorly enforced and that noncompliance may go unobserved. Conclusions: The Group urges all employers to assess the risk for third parties caused by alcohol abuse and to devise a policy on alcohol. Controlling alcoholrelated risks in the workplace calls for a better definition of the roles of Vigilance Bodies and Company Physicians together with a shift from a reactive to a proactive attitude of all the parties involved.